Malay Symbols In Malaysian Visual Art From 1970 - 2003 - Mohammad Noh, Liza Marziana; Haron, Hamdzun; Samian, Abd Latif; Hasan, Ahmadrashidi; Abd Razak, Haslinda; Mohammad Noh, Nurbaiah (2014)

(untitled)
A search for national identity in visual art begins from the resolution of National Congress of Culture in 1970s. The congress changed the local artist’s attitude and has developed awareness to in-depth study on Malay culture and Malay symbols. Traditional forms of art such as batik, woodcarving, songket, tales, legends, literature and Malay architecture has provided visual references to the artist and as a result, various styles have emerged from exploring the Malay culture in the context of form and content, which has later reshaped the Malaysian Art scene. The aim of this study is to investigate the development of Malay symbols in the Malaysian Visual Art from 1970s until 2003 and factors that contribute to it. This paper will establish the transformation of idea on the Malay culture and tradition in visual art as the art movement that was neglected in the development of Malaysian Contemporary Art. Observation will be employed, as well as books, catalogues and articles reviewed as references to investigate the development of visual art. The artwork will be examined from the Permanent Collection Inventory from 1958 to 2003 of the National Visual Art Gallery publication. A total of 298 artworks have been identified and using judgmental sampling methods, 72 artworks has been retrieved. The final data were compiled and analyzed using Minitab version 16.2.1.0. The analyses results of histogram and bar chart as well as pareto chart year are used to summarize the findings. The finding indicates that the decades of 90s has appeared to be the most active period of the resurgence of the Malay symbols in Malaysian Visual Art. However in the year 2000 to 2003, studies indicate a decline on the depiction of idea from Malay symbols by Malaysian artist. This research provides information on the development of visual art specifically on Malay symbols in Malaysian Art History and to persuade young artists to persistently utilize Malay symbols in the work of art as to preserve the national heritage.